2014
DOI: 10.1902/jop.2013.120658
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Proportion of Non‐Classic (CD14+CD16+) Monocytes/Macrophages in Peripheral Blood and Gingiva of Healthy Individuals and Patients With Chronic Periodontitis

Abstract: This study demonstrates an increased proportion of CD14+CD16+HLA-DR++ monocytes/macrophages in the peripheral blood and gingiva of patients with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
2
21
1
Order By: Relevance
“…Previous studies have reported an increase in the proportion of non-classical monocytes in periodontitis (28,29). We investigated whether peripheral monocytes from periodontitis patients (52.6 ± 5.1 years old; 2 females and 3 males) present differential S100A12 expression and secretion when compared with monocytes from periodontally healthy participants (42.4 ± 15.9 years old; 3 females and 2 males), and whether this difference was related to a particular subset.…”
Section: S100a12 Expression Is Altered In Circulating Monocytes From mentioning
confidence: 96%
“…Previous studies have reported an increase in the proportion of non-classical monocytes in periodontitis (28,29). We investigated whether peripheral monocytes from periodontitis patients (52.6 ± 5.1 years old; 2 females and 3 males) present differential S100A12 expression and secretion when compared with monocytes from periodontally healthy participants (42.4 ± 15.9 years old; 3 females and 2 males), and whether this difference was related to a particular subset.…”
Section: S100a12 Expression Is Altered In Circulating Monocytes From mentioning
confidence: 96%
“…In this study, we selected macrophages because macrophagemediated inflammatory response plays a crucial role in development of periodontal disease (Charon et al 1981;Shapira et al 1996;Jagannathan et al 2014). Results showed that LPS induced IL-6 secretion from bone marrow-derived macrophages, while PA had no effect, although it did enhance the stimulatory effect of LPS by 2-fold (Fig.…”
Section: Hfd Enhances Lps-stimulated Cytokine Expressionmentioning
confidence: 99%
“…Studies have suggested that monocytes during or after periodontal pathogen challenge could contribute to inflammation in periodontitis-associated systemic disease, such as aortic inflammation [11,12]. One study has shown an increased percentage of CD14 + CD16 + monocytes in the peripheral blood of patients with chronic periodontitis compared to healthy individuals [13] but, overall, data on peripheral blood monocyte populations in periodontitis are scarce.…”
Section: Introductionmentioning
confidence: 99%